The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.4049/jimmunol.0904011
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD93 Induces Differentiation of Monocytes and Enhances TLR Responses

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 27 publications
1
63
0
Order By: Relevance
“…CD54 (ICAM-1) is a macrophage activation marker [15] that functions as a ligand for leukocyte integrin complex to facilitate cell-cell interactions. CD54 expression is reported to be up regulated upon stimulation with macrophage stimulating factors such as GM-CSF, TLR3, TLR4 and TLR7 [14]. RBL upregulated CD54 expression in THP-1 cells comparable with the level induced by the combined treatment of PMA and LPS.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…CD54 (ICAM-1) is a macrophage activation marker [15] that functions as a ligand for leukocyte integrin complex to facilitate cell-cell interactions. CD54 expression is reported to be up regulated upon stimulation with macrophage stimulating factors such as GM-CSF, TLR3, TLR4 and TLR7 [14]. RBL upregulated CD54 expression in THP-1 cells comparable with the level induced by the combined treatment of PMA and LPS.…”
Section: Discussionmentioning
confidence: 69%
“…One of the initial events in the differentiation of monocytes to macrophage is increased adherence [14]. The kinetics of adhesion of THP-1 monocytes revealed that RBL-induced cell adhesion was delayed compared to cells stimulated with PMA.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it is known that CD93 (C1qRp) is a transmembrane receptor regulating phagocytosis and cell adhesion and is present on cells of the myeloid lineage (45). CD93 expression is increased with monocyte differentiation and macrophage activation (46,47). Targeting of Cd93 mRNA by miR-29 could promote commitment to osteoclastogenesis, preventing monocytic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…8E). NFIA expression inhibits both macrophage and osteoclast maturation, whereas GPR85 and CD93 are expressed during macrophage differentiation (13,17,46,49). Nfia and Cd93 each had two potential miR-29 binding sites in the 3Ј-UTR segment analyzed, whereas Gpr85 had one site.…”
Section: Inhibition Of Mir-29 Activity Does Not Affect the Apoptosis mentioning
confidence: 99%